Comparative kinematic analysis of release of the best Serbian shot putters - Aleksic-Veljkovic, A.; Puletic, M.; Rakovic, A.; Stankovic, R.; Bubanj, S.; Stankovic', D. (Facta Universitatis: Series Physical Education and Sport, 2011)
In recent years there have been a number of researchers studying the techniques of shot put parameters and factors that are crucial for achieving top results, as well as those necessary for optimal performance. The aim of this study was to determine differences in the parameters of release of top Serbian athletes. The throwing technique was taken at the Serbian Cup 2011 for the competitors who achieved the best results. The values of the variables were determined by using software for 2D kinematic analysis, "Human", version 6.0 HMA Technology Inc. 2005, United States of America (Human). The first place contestant scored a higher release speed of 13m/s (13.79m/s), while the speed of the second and the third was much lower (11.9m/s and 11.68m/s). The maximum height of release was determined for the second-placed competitor (2.22m), then for the first-placed (2.07m) and the third-placed competitor (2.05m). The angle of release for the top-placed competitor was 40.4°, 42.8° for second placed and 41° for the third placed. In the case of the top-ranked competitor and the third there is the possibility of increasing the horizontal length of the shot put, which would lead to greater distance. The significance of this research is to obtain useful information for coaches and athletes, which will contribute to the further improvement of techniques. It is necessary to conduct further and more detailed studies of phases preceding the release, on which the proper performance of the release phase and achievement of the best possible results depends.